Hubungan antara Pembelajaran Berbasis Kontekstual dengan Pembentukan Akhlak Siswa (Studi pada Mata Pelajaran Lingkungan Hidup di SMAN Kota Tasikmalaya) - Abdurrahman, Nana Herdiana (JPPI | Jurnal Penelitian Pendidikan Islam, 2018)
This study aims to determine the relationship between contextual based learning with the formation of morals in the maintenance of the environment of the State Senior High School in Tasikmalaya City. The study used descriptive method, with the number of samples as much as 240. Data analysis using correlation test resulted in correlation coefficient of 0.680 and significant at the level of trust 0.05. Thus, contextual based learning is positively related to morality in the maintenance of the school environment